Hand Hygiene Practices among Nurses in South Sulawesi Hospitals - Muhammad Rizky Asfarada; Rini Rachmawaty; Andina Setyawati; Gulzar Malik (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Healthcare professionals’ adherence to hand hygiene protocols is paramount to prevent Healthcare-Associated Infections (HAIs) and ensure patient safety. This study evaluates compliance with the World Health Organization's (WHO)